Microfluidic Technologies for Human Health. - Demirci, Utkan (World Scientific, 2012)
The field of microfluidics has in the last decade permeated many disciplines, from physics to biology and chemistry, and from bioengineering to medical research. One of the most important applications of lab-on-a-chip devices in medicine and related disciplines is disease diagnostics, which involves steps from biological sample/analyte loading to storage, detection, and analysis. The chapters collected in this book detail recent advances in these processes using microfluidic devices and systems. The reviews of portable devices for diagnostic purposes are likely to evoke interest and raise new.